2020
DOI: 10.3389/fpsyg.2020.604412
|View full text |Cite
|
Sign up to set email alerts
|

Belonging and Social Integration as Factors of Well-Being in Latin America and Latin Europe Organizations

Abstract: BackgroundStudies and meta-analyses found individual, meso and micro-social factors that are associated with individual well-being, as well as a positive socio-emotional climate or collective well-being.AimThis article simultaneously studies and examines these factors of well-being.MethodWell-Being is measured as a dependent variable at the individual and collective level, as well as the predictors, in three cross-sectional and one longitudinal studies. Education and social intervention workers (N = 1300, K = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 139 publications
(208 reference statements)
0
7
0
Order By: Relevance
“…For example, it has been shown that living in a highly segregated inner-city neighborhood often limits black and minority residents' chances of escaping poverty, deprivation, and isolation due to poor social networks, limited local resources and constrained job opportunities ( 60 – 62 ). Previous research shows that a non-threatening psychological climate, characterized by comradeship and mutual support, is encouraged by open and fluid communication, whereas undesirable life events negatively influence social integration and participation over time ( 63 ). Psychological research indicates, therefore, that segregation is associated with negative emotional outcomes ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that living in a highly segregated inner-city neighborhood often limits black and minority residents' chances of escaping poverty, deprivation, and isolation due to poor social networks, limited local resources and constrained job opportunities ( 60 – 62 ). Previous research shows that a non-threatening psychological climate, characterized by comradeship and mutual support, is encouraged by open and fluid communication, whereas undesirable life events negatively influence social integration and participation over time ( 63 ). Psychological research indicates, therefore, that segregation is associated with negative emotional outcomes ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the load of mourning have revealed an increased risk of adverse health consequences, including suicide, after death [ 26 ]. With variables including a lack of social integration, a poor feeling of belonging, and inadequate social support, it is thought that losing close relatives is a traumatic event linked with an increased risk of self-harm or suicide [ 27 ]. According to Mogensen et al [ 28 ], suicide rates were most significant six months after losing a family member or close relative.…”
Section: Reviewmentioning
confidence: 99%
“…Previous works (Chang and Hsieh 2018;Pradenas et al 2021;Chanda and Goyal 2020;Da Costa et al 2020) have studied this relationship from a management perspective to enhance the company's performance. Little has been written about the advantages of this relationship for investors interested in Environmental, Social, and Governance (ESG) criteria.…”
Section: Introductionmentioning
confidence: 99%